A Comparison of Factors Related to Academic Achievement in English Between Study Plans of Mathayom Suksa Five Student - Thankham, Phetcharin; Srihaset, Kamontip; Tippayakulpairoj, Darunee (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Learning English aims to communicate, gain knowledge, and have further education. Anyway, the differences in prior knowledge and the capabilities of students are important factors that can cause the difference in English learning achievements. In this thesis, the researcher examines factors related to 1) The learning achievement in English of Matthayom Suksa Five students and 2) compares factors related to learning achievement in English between the study plans of Matthayom Sueksa Five students. Methodology: The research population was Matthayom Suksa Five students at schools under the jurisdiction of the Secondary Educational Service Area Office One, Bangkok Metropolis. Employing the multistage sampling method, the researcher collected a sample population of 636 students. The research instrument was a questionnaire, which had a reliability of 0.97. The data collected were subsequently analyzed by One-way MANOVA. Results: (1) The study of factors related to learning achievement in English of Matthayom Sueksa Five students showed the following: The variable with the highest weight for classificatory function was previous knowledge (a mean of 71.98). Next in descending order were motivation toward the study of English (a mean of 4.16), teaching quality of teacher (a mean of 4.03), learning atmosphere (a mean of 3.84), learning behavior (a mean of 3.47), attitudes toward the study of English (a mean of 3.20), and family relationships (a mean of 3.12) and (2) The study of comparison of factors related to learning achievement in English between study plans of Matthayom Sueksa Five students exhibited attitudes toward the study of English, learning behavior, teaching quality of teacher, learning atmosphere, and previous knowledge were different between study plans at the statistically significant level of .05. and motivation toward the study of English, and family relationships were no differences. Conclusion: The study underscores the critical influence of various factors on learning achievement in English among Matthayom Sueksa Five students, with previous knowledge identified as the most significant determinant. Additionally, the comparison across study plans reveals noteworthy variations in specific factors, indicating the importance of considering diverse aspects for targeted interventions. These findings contribute valuable insights for educators and policymakers aiming to enhance English education outcomes by addressing the nuanced interplay of individual and contextual elements.